2023
DOI: 10.3390/jcm12020547
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke Induces Skeletal Muscle Damage and Alters Transcriptome Profile in Rats

Abstract: To establish pathological features of skeletal muscle post-stroke and to provide a background for promising interventions. Adult male SD rats were selected and randomly divided into a control group, a sham group, and a middle cerebral artery occlusion (MCAO) group. The tolerance and capability of exercise were separately collected on days 1, 3, 5, and 7 after the MCAO operation. The neurological deficits, brain infarct volume, soleus histopathology, mRNA-seq analysis, flow cytometry, immunofluorescence, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Notably, the non‐impaired rats (control, 1 and 2 weeks) had regular fascicle structures. In a bilateral comparison after stroke, characteristics of muscle atrophy from the 1 week (impaired) group were observed, leading to a decrease in the volume of muscle fibers (Qi et al, 2023). In particular, a qualitative evaluation revealed that the empty space was expanding, as severe symptoms clearly appeared in the 2 weeks (impaired) group.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the non‐impaired rats (control, 1 and 2 weeks) had regular fascicle structures. In a bilateral comparison after stroke, characteristics of muscle atrophy from the 1 week (impaired) group were observed, leading to a decrease in the volume of muscle fibers (Qi et al, 2023). In particular, a qualitative evaluation revealed that the empty space was expanding, as severe symptoms clearly appeared in the 2 weeks (impaired) group.…”
Section: Resultsmentioning
confidence: 99%
“…This decline in the CSS group might be traced back to several factors, including neural damage resulting from stroke [57], which may lead to inefficient neurotransmission of electrical signals from neurons to muscles. This inefficiency, along with neural reorganization within the central nervous system [58], may potentially cause a decrease in muscle mass [59].…”
Section: Discussionmentioning
confidence: 99%